In-silico modelling of the mitogen-activated protein kinase (MAPK) pathway in colorectal cancer: mutations and targeted therapy - Sommariva, Sara; Berra, Silvia; Biddau, Giorgia; Caviglia, Giacomo; Benvenuto, Federico; Piana, Michele (Frontiers in Systems Biology, 2023)
Introduction: Chemical reaction networks (CRNs) are powerful tools for describing the complex nature of cancer’s onset, progression, and therapy. The main reason for their effectiveness is in the fact that these networks can be rather naturally encoded as a dynamical system whose asymptotic solution mimics the proteins' concentration profile at equilibrium. Methods and Results: This paper relies on a complex CRN previously designed for modeling colorectal cells in their G1-S transition phase and presents a mathematical method to investigate global and local effects triggered on the network by partial and complete mutations occurring mainly in its mitogen-activated protein kinase (MAPK) pathway. Further, this same approach allowed the in-silico modeling and dosage of a multi-target therapeutic intervention that utilizes MAPK as its molecular target. Discussion: Overall the results shown in this paper demonstrate how the proposed approach can be exploited as a tool for the in-silico comparison and evaluation of different targeted therapies. Future effort will be devoted to refine the model so to incorporate more biologically sound partial mutations and drug combinations.